The story of scripture : an introduction to biblical theology - Emerson, Matthew Y., 1984-; Thomas, Heath (Nashville, Tennessee : B & H Academic, 2017)
The Story of Scripture provides practical, Christ-centered ways that we can read the Bible as one book.
Introduction : what is biblical theology? -- The story of the Bible. Part 1 -- The story of the Bible. Part 2, Redemption, continued -- The story of the Bible. Part 3, The New Testament -- Exploring biblical terrains -- Using the map : practical applications for biblical theology.
Includes bibliographical references and index.
Master record variable field(s) change: 050
Keywords: Bible -- Theology; Bible; BIBLES -- General; RELIGION -- Biblical Reference -- General; RELIGION -- Biblical Reference -- Handbooks; Theology; Electronic books